Waterpipe tobacco smoking prevalence among young people in Great Britain, 2013–2016. (18th December 2017) - Jawad, Mohammed; Cheeseman, Hazel; Brose, Leonie S
Abstract: Background: One percent of adults in Great Britain use waterpipe tobacco at least monthly, however national epidemiological evidence among young people is absent. This study aims to assess waterpipe tobacco prevalence and correlates among young people in Great Britain. Methods: Data were analyzed from online surveys conducted annually from 2013 to 2016 with weighted national samples of 11 to 18-year olds in Great Britain (annual n = 1936–2059). Primary outcome measures were at least monthly waterpipe tobacco use and lifetime waterpipe tobacco use. Binary logistic regression models tested the association between these outcomes and age, sex, country of residence and other tobacco consumption. Results: Between 2013 and 2016, 1.7% (95% CI 1.5–2.1%) used waterpipe tobacco at least monthly and 9.9% (95% CI 9.2–10.7%) used waterpipe in their lifetime. There were no changes in prevalence over time. At least monthly use was associated with older age groups [16–18 years vs. 11–15 years, adjusted odds ratio (AOR) 2.63, 95% CI 1.55–4.46], male sex (AOR 1.82, 95% CI 1.23–2.71) and other tobacco consumption (e.g. lifetime cigarette use AOR 10.30, 95% CI 5.22–20.29). Lifetime use had similar correlates, but was not associated with male sex (AOR 0.97, 95% CI 0.80–1.17). Conclusions: One in 10 young people in Great Britain have tried waterpipe tobacco, though more frequent use appears low. We found no evidence of increasing or decreasing prevalence of waterpipe use between 2013 and 2016. Being male, older and a concurrent user of other tobacco products were correlated with waterpipe tobacco use.